PENGARUH LABEL HALAL, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN YANG BERDAMPAK PADA MINAT BELI ULANG PRODUK SABUN PEMBERSIH WAJAH X DI JABODETABEK DAN SURABAYA - Risetyaningsih, Ayunanda; Yantih, Novi; Derriawan, Derriawan (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
One of the determining factors in repurchasing a product is the halal factor. Especially for the people of Indonesia is one of the country with the largest Muslim population in the world. Because of this, the government issued Republic of Indonesia Law Number 33 of 2014 concerning Guaranteed Halal Products, that not all products circulating in society are guaranteed to be halal. X facial wash is one of the products that has received a halal certificate and Top Brand Award for 3 consecutive years (2020-2022) in the first place for facial wash category. This study aims to determine whether there is an effect of the halal label, price, and product quality on purchasing decisions and whether there is an impact on repurchasing intention for X facial wash. The method used is descriptive quantitative and collecting data through questionnaires. Data analysis using SEM (Structural Equation Modeling) technique. The number of respondents was 235 people who had purchased and used X Facial Wash product during the last 6 months. Data analysis shows that halal label, price, and product quality have an effect on purchasing decisions, but have no effect on repurchasing. This means the existence of a halal label, affordable prices, and the quality of X facial wash products are the determining factors for consumers to purchase products, but not for repurchasing. The halal label, price and product quality can be used to determine consumers' purchasing decisions, but for repeat purchases, efforts are still needed to dig deeper into the determining factors.